O DESAFIO DO ASSOCIATIVISMO NA AGRICULTURA FAMILIAR: o caso dos Produtores Rurais Feirantes do Município de Pato Branco-PR PONTA GROSSA 2007 - Aguiar, Audrey Merlin Leonardi de (2007)
The objective of this study consisted in constructing possibilities that contributed for the understanding of the perceptions and meanings attributed to the associativeness from the social representations of the trader familiar agriculturists in the city of Pato Branco. The technique of data collection used was the case study, with quantitative and qualitative approaches, arranged in half-structuralized interviews, in whose stories of the associates they had retraced their experience in the collective performance. The theoretical references used in this study join to the multi dimensions of the life histories of the familiar agriculturists, who had constructed from their social representations, an associativeness model as an alternative form of participating of the local market. The refined results demonstrate through their cultural identities, associative experience, challenges and opportunities the necessity of the implementation of new forms of management that stimulate the collective involvement and the participation of the associates.